Exploring positive youth development through mentoring and coaching in sports - Lee, Kwan Meng; Ismail, Ismi Arif; Eric Krauss, Steven; Arshad, Mohd Mursyid (Innovare Academics Sciences, 2020)
In the sporting world, coaching has always been the primary instructional approach that is employed to develop athletes’ performance. That is because sports have often been equated with performance at elite levels in competitions, tournaments, championships, and professional sports. It has never been focused on human development, including in youth development. Mentoring is rarely been mentioned in sports though it does have a role in sport athlete development. Employing mentoring and coaching in sports takes different approaches, and so are its goal and objectives. Nevertheless, both mentoring and coaching can complement and support each other in developing the youth athlete. Little however is known about how mentoring can be employed in sports. This paper therefore explores, examines and discusses the distinctions between both mentoring and coaching and how they contribute to positive youth development through sports participation. It discusses their distinctions, and present the two pathways of sports and recreation in youth development through mentoring and coaching. The outcomes and benefits of mentoring and coaching contributes to the holistic and performance development of the youth athlete.